Interaction of hydronium ion with dibenzo-18-crown-6: NMR, IR, and theoretical study - Kríz, Jaroslav; Dybal, Jirí; Makrlík, Emanuel; Budka, Jan (The journal of physical chemistry. A, 2008)
Interaction of dibenzo-18-crown-6 (DBC) with H 3O (+) (HP) in nitrobenzene- d 5 and dichloromethane- d 2 was studied by using (1)H and (13)C NMR spectra and relaxations, FTIR spectra, and quantum chemical DFT calculations. NMR shows that the DBC*HP complex is in a dynamic equilibrium with the reactants, the equilibrium constant K being 0.66 x 10 (3), 1.16 x 10 (4), and 1.03 x 10 (4) L x mol (-1) in CD 2Cl 2, nitrobenzene, and acetonitrile, respectively. The complex appears to have a C 2 v symmetry in NMR, but FTIR combined with DFT normal mode calculations suggest that such high symmetry is only apparent and due to exchange averaging of the structure. FTIR spectra as well as energy-optimized DFT calculations show that the most stable state of the complex in solution is that with three linear hydrogen bonds of HP with one CH 2-O-CH 2 and two Ar-O-Ar oxygen atoms. The structure is similar to that found in solid state but adopts a somewhat different conformation in solution. The dynamics of exchange between bound and free DBC was studied by NMR transverse relaxation. It was found to be too fast to give reproducible results when measured with the ordinary CPMG sequence or its variant DIFTRE removing residual static dipolar interaction, but it could be established by rotating-frame measurements with high intensity of the spin-lock field. The correlation time of exchange was found to be 5.6 x 10 (-6) and 3.8 x 10 (-6) s in dichloromethane and nitrobenzene, respectively. Such fast exchange can be explained by cooperative assistance of present water molecules.
Keywords: vodíková vazba; Crown Ethers; spektroskopie infračervená s Fourierovou transformací; Quantum Theory; Computer Simulation; Magnetic Resonance Spectroscopy; magnetická rezonanční spektroskopie; kvantová teorie; počítačová simulace; crown ethery; Reference Standards; Onium Compounds; referenční standardy; Hydrogen Bonding; Spectroscopy, Fourier Transform Infrared; chemické modely; izotopy uhlíku; Carbon Isotopes; molekulární struktura; Models, Chemical; Protons; oniové sloučeniny; Molecular Structure; protony